Polymorphism of Transcription Factor 7-Like 2 Gene and HOMA-β Level of Individuals With and Without Type 2 Diabetes Mellitus Family History - Waode Astria Sahrani; Indwiani Astuti; Ahmad Hamim Sadewa (Indonesian Journal of Biotechnology, 2014)
Family history has considered as a risk factor of type 2 diabetes. Transcription factor-7 like 2 (TCF7L2) hasrole to regulates insulin secretion and blood glucose homeostasis. The aim of current study was to determine thers7903146 polymorphism of TCF7L2 gene and homeostatic model assessment-β (HOMA-β) level on individual withand without type 2 Diabetes Mellitus (DM) family history. This work is a case-control study. Thirty six subjectswith type 2 DM family history and 36 subjects without type 2 DM family history were recruited. HOMA-βmeasure to analyze the insulin secretion. Polymorphisms of TCF7L2 gene was analyzed by using PCR-RFLPmethod. Statistical analysis was performed by using T-test, Mann-Whitney and Chi-square with signifi cancelevel 0.05. The frequency of the T allele of the cases were 4.2% and the controls were 2.8% (p=0.500). The oddratio was 0.649 (CI;95%:0.106-4.055). The HOMA-β levels of the cases were signifi cant low (132.56±62.48)compared with the controls (266.09±1.68) with p=0.000. The subjects with type 2 DM family history have asimilar frequency of having T alleles and CT/TT genotypes. The subjects with type 2 DM family history hassignifi cantly lower HOMA-β levels than subject without DM family history.